Pengaruh Distributive Justice dan Procedural Justice Terhadap Organizational Citizenship Behavior Toward Organization dengan Affective Commitment Sebagai Variabel Mediasi pada Dinas Sosial Kabupaten Bangkalan - Fikri Dainuri Iqbal; Praptini Yulianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In today's globalised bureaucracy, it is not enough for employees to simply do the job they were hired to do. Many agencies expect their members to not only focus on and complete their own main tasks, but also proactively help their colleagues and the organisation, therefore, OCB is important in today's world of bureaucrats, where organisations must be increasingly effective to survive. As a result, researchers are encouraged to develop a deeper understanding of the variables associated with OCB. This study aims to determine the effect of distributive justice and procedural justice variables on OCB and also the mediating effect of affective commitment on the relationship between the two. The results showed that distributive justice and procedural justice had a significant positive effect on affective commitment, affective commitment had a significant positive effect on OCB aimed at the organisation (OCB-O), distributive and procedural justice had an insignificant positive effect on OCB aimed at the organisation (OCB-O), and affective commitment was partially proven to mediate the relationship between distributive and procedural justice with OCB-O.